Chasing the Mirage of Complete Health: Revisiting WHO's Definition of Health in Modern Health Paradigms - Elmuttalut, Mohammed (International Journal of Innovative Research in Medical Science, 2024)
The World Health Organization’s (WHO) in 1948 defined health as a "state of complete physical, mental, and social well-being, and not merely the absence of disease or infirmity" which had been influential yet controversial among public health scholars. This critical review examined the limitations of the WHO definition through an analysis of contemporary literature. Key limitations identified include its static and idealistic nature, inadequacy in accommodating the needs of individuals with chronic illnesses and aging populations, and as well the limited cultural and spiritual relevance and inclusivity. The findings of this review emphasized the need for a more adaptable, resilient, inclusive definition of health that reflects the dynamic and complex realities of health in the 21st century, with implications for policy, clinical and public health practices, and global health frameworks.